The Mathematical Modelling of Refuse Build-up on the University Campus: A Case Study of KNUST Campus (European Journal of Pure and Applied Mathematics, 2019)
In this paper, xyzw model is introduced which characterizes the solid waste generated by the four departments in the university. Thus, the refuse on the street x, in the gutters y, in the dustbins z and dumpsite w. From the qualitative analysis of xyzw model, it revealed that the refuse in these departments piles up as the time increases indeï¬nitely. Based on the analysis of data from the KNUST campus the refuse keeps on piling up. This reveals that the trucks are not able to adequately carry refuse from three departments: street, gutters and dustbins to the dumpsite as expected by the university authority. This comes as a result of overï¬‚ows from the dustbins at some vantage points in the university. In practice, the waste in gutters and on street are collected and deposit it in these dustbins (with varying volumes) everyday, but the trucks are not able to convey all the quantum of waste in these dustbins to the dumpsite thereby resulting in refuse pile up on campus of the university